1995
DOI: 10.1161/01.cir.92.10.2975
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor Expression in Human Saphenous Veins

Abstract: These results indicate that human saphenous veins from both sexes express PR, as previously described for arterial blood vessels. This observation suggests that progesterone acts directly on these veins via a classic receptor-mediated pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
38
1
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
4
38
1
2
Order By: Relevance
“…The role of progestogens in the alteration of vessels blood flow and in the development of varicose veins warrants further study. 36 One potential limitation of our study is that observational studies are subject to bias. The validity of the ESTHER study has been discussed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The role of progestogens in the alteration of vessels blood flow and in the development of varicose veins warrants further study. 36 One potential limitation of our study is that observational studies are subject to bias. The validity of the ESTHER study has been discussed.…”
Section: Discussionmentioning
confidence: 96%
“…28 The occurrence of venous stasis during luteal phase or pregnancy, together with the presence of estrogen and progesterone receptors in the venous wall, 36 suggests that venous blood flow may be directly modulated by steroid hormones. Therefore, norpregnane derivatives, which have a high progestational activity, might increase the VTE risk through venous stasis via a progesterone receptormediated pathway.…”
Section: Discussionmentioning
confidence: 99%
“…27 The occurrence of venous stasis, especially observed during pregnancy and the luteal phase, could be modulated by steroid sex hormones via progesterone receptors which are present in the venous wall. 40 Therefore, an increase in progestational activity of progestins, especially norpregnanes, compared to micronized progesterone might further alter blood flow and increase thrombotic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Direct effects of sex steroids on human veins have been postulated by a number of investigators [1,2,3,4,5,6] . Karas et al reported the presence of ER in smooth muscle cells of human saphenous vein, although at a low level [4] but Perrot-Applanat et al reported that ER and its mRNA were undetectable in 80% of saphenous veins examined [6].…”
Section: Discussionmentioning
confidence: 99%
“…VARIOUS clinical and epidemiological observations suggest that sex steroids play an important role in the function and pathology of human veins [1][2][3]. Karas et al recently demonstrated the presence of estrogen receptor (ER) in smooth muscle cells cultured from surgical specimens of non-pathological human saphenous veins removed for coronary artery bypass surgery [4].…”
mentioning
confidence: 99%